We still here : hip hop north of the 49th parallel - Marsh, Charity, 1974-; Campbell, Mark V. (McGill-Queen's University Press, 2020)
"We Still Here maps the edges of hip-hop culture and makes sense of the rich and diverse ways people create and engage with hip-hop music within Canadian borders. Contributors to the collection explore the power of institutions, mainstream hegemonies, and the processes of historical formation in the evolution of hip-hop culture. Throughout, the volume foregrounds the generative issues of gender, identity, and power, in particular in relation to the Black diaspora and Indigenous cultures. Exposing the distinct inner mechanics of Canadian hip hop from a variety of perspectives. The contributions of artists in the scene are front and centre in this collection. By amplifying rarely heard voices within hip-hop culture, We Still Here argues for its power to disrupt national formations and highlights the people and communities who make hip hop happen."--